Causal attributions for poverty in citizens of Córdoba (Argentina): Psychometric analysis using CTT and IRT - Reyna, Cecilia (2024)
Fil: Reyna, Cecilia. Universidad Nacional de Córdoba. Facultad de Psicología; Argentina.